Elements and principles of design - Adkins, John R.; Crystal Productions (Glenview, IL: Crystal Productions, 1989)
Couch demonstrates how to create dynamic compositions using the various elements of design
Editors, Donna Gulick, John R. Adkins ; executive producer, Tom & Larry Hubbard
Hosted by Tony Couch
Keywords: Design; Watercolor painting -- Technique